Evaluation of an integrated 3D‐printed phantom for coronary CT angiography using iterative reconstruction algorithm. Issue 3 (27th March 2020) - Abdullah, Kamarul A.; McEntee, Mark F.; Reed, Warren; Kench, Peter L.
Abstract: Introduction: 3D‐printed imaging phantoms are now increasingly available and used for computed tomography (CT) dose optimisation study and image quality analysis. The aim of this study was to evaluate the integrated 3D‐printed cardiac insert phantom when evaluating iterative reconstruction (IR) algorithm in coronary CT angiography (CCTA) protocols. Methods: The 3D‐printed cardiac insert phantom was positioned into a chest phantom and scanned with a 16‐slice CT scanner. Acquisitions were performed with CCTA protocols using 120 kVp at four different tube currents, 300, 200, 100 and 50 mA (protocols A, B, C and D, respectively). The image data sets were reconstructed with a filtered back projection (FBP) and three different IR algorithm strengths. The image quality metrics of image noise, signal–noise ratio (SNR) and contrast–noise ratio (CNR) were calculated for each protocol. Results: Decrease in dose levels has significantly increased the image noise, compared to FBP of protocol A ( P < 0.001). As a result, the SNR and CNR were significantly decreased ( P < 0.001). For FBP, the highest noise with poor SNR and CNR was protocol D with 19.0 ± 1.6 HU, 18.9 ± 2.5 and 25.1 ± 3.6, respectively. For IR algorithm, the highest strength (AIDR3Dstrong ) yielded the lowest noise with excellent SNR and CNR. Conclusions: The use of IR algorithm and increasing its strengths have reduced noise significantly and thus increased the SNR and CNR when compared to FBP. Therefore, this integrated 3D‐printed phantom approach could be used for dose optimisation study and image quality analysis in CCTA protocols. Abstract : This article acknowledges the use of 3D‐printing to develop a phantom for CT dose optimisation study. A 3D‐printed cardiac insert phantom was positioned into an anthropomorphic chest phantom and scanned with a multi‐slice CT scanner. An objective image analysis was performed. In summary, this phantom could be used for dose optimisation study especially when evaluating iterative reconstruction (IR) algorithm.